The work and family role orientations of STEM students - Nzima, Ntombeziningi (Organisational Psychology, 2017)
Students in the future can expect to partake in two life roles as adults: a work role and family role. This study investigated the life role salience of students studying science, technology, engineering and mathematics (N = 191) and examined the extent to which their gender role ideology and perceived parental work-family conflict are predictors of life role salience. Regression analysis showed that students with traditional gender role ideologies had greater family role salience and students with egalitarian gender role ideologies had greater work role salience. Further analysis showed that students' family role salience was predicted by the work-family conflict of their same-sex parent. The implications of the findings and suggestions for future research are discussed.